2018
DOI: 10.1007/s00464-018-6226-9
|View full text |Cite
|
Sign up to set email alerts
|

Does near-infrared (NIR) fluorescence angiography modify operative strategy during emergency procedures?

Abstract: IntroductionBowel viability can be difficult to evaluate during emergency surgery. Near-infrared (NIR) fluorescence angiography allows an intraoperative assessment of organ perfusion during elective surgery and might help to evaluate intestinal perfusion during emergency procedures. The aim of this study was to assess if NIR modified operative strategy during emergency surgery.Materials and methodsFrom July 2014 to December 2015, we prospectively evaluated all consecutive patients, who had NIR assessment durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 20 publications
1
20
0
3
Order By: Relevance
“…In particular, three out of four patients who underwent bowel resection and primary anastomosis suffered from anastomotic leak, which directly lead to mortality, suggesting that the use of an earlier second-look laparotomy and/or a prophylactic stoma should be considered in such patients. Modern surgical techniques, such as fluorescent angiography for the verification of intraoperative vascular perfusion, might have a positive effect on the prognosis of those who are predisposed to postoperative anastomotic leak [24]. We also found that the peritoneal irritation sign, several laboratory findings on admission (BE, lactate, NLR, and CRP), and IP on CT represented potential prognostic factors for bowel ischemia in the full cohort with HPVG, although this finding was based on univariable analyses, because of the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, three out of four patients who underwent bowel resection and primary anastomosis suffered from anastomotic leak, which directly lead to mortality, suggesting that the use of an earlier second-look laparotomy and/or a prophylactic stoma should be considered in such patients. Modern surgical techniques, such as fluorescent angiography for the verification of intraoperative vascular perfusion, might have a positive effect on the prognosis of those who are predisposed to postoperative anastomotic leak [24]. We also found that the peritoneal irritation sign, several laboratory findings on admission (BE, lactate, NLR, and CRP), and IP on CT represented potential prognostic factors for bowel ischemia in the full cohort with HPVG, although this finding was based on univariable analyses, because of the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, three out of four patients who underwent bowel resection and primary anastomosis suffered from anastomotic leak, which directly lead to mortality, suggesting that the use of an earlier second-look laparotomy and/or a prophylactic stoma should be considered in such patients. Modern surgical techniques, such as fluorescent angiography for the verification of intraoperative vascular perfusion, might have a positive effect on the prognosis of those who are predisposed to postoperative anastomotic leak [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern surgical techniques, such as uorescent angiography for the veri cation of intraoperative vascular perfusion, might have a positive effect on the prognosis of those who are predisposed to postoperative anastomotic leak [21].…”
Section: Discussionmentioning
confidence: 99%
“…These tools include Laser Doppler Flowmetry (LDF) and fluorescence imaging (FI). The former method is one of the pioneers in gut perfusion assessment [ 13 , 14 , 15 , 16 , 17 ], whereas the latter is widely used in contemporary clinical practice [ 18 , 19 , 20 , 21 ]. Note that the use of LDF has not become widespread in AMI affected patients, even though the method continues to be of interest in experimental studies of intestinal tissue damage following ischemia/reperfusion injury [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%